2019
DOI: 10.3762/bjoc.15.24
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free C–H mercaptalization of benzothiazoles and benzoxazoles using 1,3-propanedithiol as thiol source

Abstract: A facile and effective C–H functionalization strategy for the synthesis of 2-mercaptobenzothiazoles and 2-mercaptobenzoxazoles is described. 1,3-Propanedithiol was employed to convert benzothiazoles and benzoxazoles to the corresponding heteroarylthiols in the presence of potassium hydroxide and DMSO. This novel protocol is featured by direct C–H mercaptalization of heteroarenes and a simple reaction system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…1) constitute a very interesting compound family due to their applications not only in organic synthesis, but also in the biomedical field as antibacterial, antiviral, anti-inflammatory, analgesic and anthelmintic agents. [13][14][15][16][17] Moreover, interesting studies have shown that the complexes of 2-mercaptobenzoxazoles with various transition metals possess a cytotoxic activity against cancer cells. 18…”
mentioning
confidence: 99%
“…1) constitute a very interesting compound family due to their applications not only in organic synthesis, but also in the biomedical field as antibacterial, antiviral, anti-inflammatory, analgesic and anthelmintic agents. [13][14][15][16][17] Moreover, interesting studies have shown that the complexes of 2-mercaptobenzoxazoles with various transition metals possess a cytotoxic activity against cancer cells. 18…”
mentioning
confidence: 99%
“…Benzoxazole ring containing antibiotic, calcymicin reported by Evans 4 . Benzoxazole moieties are also reported to exhibit various biological activities like antihistaminic activity 5 , antimicrobial activity, analgesic 6 , antiinflammatory activity 7 , anti-mycobacterial 8 , anticancer 9 , anthelmintic activity 10 , hypoglycaemic activity 11 , antiviral 12 , herbicidal 13 , diuretic and uricosuric activities 14 .…”
mentioning
confidence: 99%